A mathematical model of the calendered exiting thickness of micropolar sheet. Issue 3 (9th June 2017) - Ali, Nasir; Atif, Hafiz Muhammad; Javed, Muhammad Asif; Sajid, Muhammad
Abstract : A theoretical analysis based on the lubrication theory is presented to study the calendering mechanism. The material to be calendered is described by the constitutive relationship of a micropolar fluid. An exact solution and numerical solution of the problem is calculated. The roll‐separating force, power function and exiting sheet thickness are computed numerically using Runge‐Kutta method. The influence of the material parameters on the pressure distribution, pressure gradient and related quantities of engineering interest in calendering process is analyzed through graphs. POLYM. ENG. SCI., 58:327–334, 2018. © 2017 Society of Plastics Engineers